Paylater Mindset: The Shift in Gen Z's Thinking Towards Debt from a Sharia Perspective - Rizaldy Alpiansyah; Isrun Abdurahman; Irfan Alkhotiri; Miftah Wangsadanureja; Dzulfikri (Dirham : Journal of Islamic Economics, 2026)
Digital disruption in the modern economic landscape has given birth to financial technology (fintech) instruments that radically change the consumption patterns and financial governance of society globally and nationally. One of the most dominating innovations that has sparked sharp discourse is the Buy Now, Pay Later (BNPL) service, more popularly known as paylater. Generation Z (Gen Z) and Millennials are recorded as the largest demographic of users in this service ecosystem, where the total outstanding paylater debt in Indonesia reached an aggregate figure of Rp29.59 trillion in April 2025, with a Non-Performing Loan (NPL) ratio that continues to creep up. This scientific report presents a comprehensive, in-depth, and nuanced analysis of the fundamental shift in Generation Z's mindset towards the concept of debt due to paylater penetration, evaluated strictly through the lens of Islamic economics, Fiqh Muamalah, and Maqashid Sharia. Through a synthesis of empirical data from the Financial Services Authority (OJK), behavioral economics literature, and fatwas from the National Sharia Board of the Indonesian Ulema Council (DSN-MUI), this research identifies an acute sociological shift: debt, which in Islamic tradition is inherently viewed as an emergency instrument based on mutual assistance (tabarru'), is now commodified into a lifestyle based on instant gratification and a "self-reward" culture that reduces the psychological friction of shopping (pain of paying). Furthermore, the analysis in this report outlines contemporary Fiqh Muamalah resolutions regarding the schemes of Istijrar, Murabahah, Wakalah bil Ujrah, Qardh, and Kafalah to strictly differentiate between conventional paylater and sharia paylater facilities. Within the framework of Maqashid Sharia, the normalization of consumptive debt among Gen Z is proven to be diametrically opposed to the principle of Hifz al-Mal (protection of wealth), triggering systemic threats in the form of israf (extravagance) and tabzir (extreme wastefulness). In conclusion, the report asserts that without structured, massive, and digitally integrated Islamic financial literacy interventions, the ease of access to instant credit can transform from a tool of financial inclusion into a trap of long-term financial fragility that undermines the economic resilience of future generations.